Dynamics of motor activity of women in the first period of mature age under the influence ofa program of independent health-oriented classess - Dziuba , L. (Sportyvnyi Visnyk Prydniprovia, 2025)
Introduction. Analysis of modern research demonstrates a significant decrease in the level of physical activity of women, as one of the leading factors that negatively affect the health status, level of psycho-emotional state and functional working capacity of the adult population. The purpose of the study is to investigate the impact of the program of independent physical education and health classes on the level of physical activity of women of the first period of mature age who are engaged in mental work. Methods: analysis and generalization of data from scientific and methodological literature, pedagogical experiment, timing of physical activity, methods of mathematical statistics. The study involved 47 women aged 25–35 years. The program was implemented during 2024–2025 in three consecutive stages: preparatory, main and support. The structure of the classes combined the main means of physical education and health-improving orientation, which were used in the weekly cycle: daily morning gymnastics, daily physical education breaks during the working day, three-time evening relaxation complexes and two-time training in the chosen orientation – strength or aerobic direction or fitness yoga. The results showed a significant increase in total daily energy expenditure (p<0.001), a decrease in the share of sedentary mode (from 44% to 35.5%) and an increase in time at the basic, average and high levels of physical activity during the experiment. The greatest positive changes were recorded in the second stage of the program, which is explained by the increase in the volume and intensity of training. The developed program combines physiological feasibility and psychological attractiveness, ensuring the constant involvement of women in health-improving physical activity. Its advantage lies in the possibility of including exercises in the daily schedule without interruption from professional duties. Conclusions. The obtained data confirm the effectiveness of independent physical education and health-improving classes in increasing the level of motor activity and energy metabolism of women engaged in mental work. This allows us to recommend the program as a mean of preventing hypodynamia and psycho-emotional exhaustion.